A Review on Texture Feature Analysis Based Watermarking Scheme for Image Processing - Kaur, Pardeep; Shalini, (International Journal of Computer Sciences and Engineering, 2018)
The digital watermarking is the technique which is used to provide security to sensitive data which is stored in the form of image. The watermarking is the process in which features of the original and sensitive image is calculated and in the second step, the original image is embedded into the watermark image. In this research paper, the neural network based watermarking technique is improved using GLCM and PCA algorithm. The GLCM and PCA algorithm extracts the features of the original image. The output of PCA algorithm defines the scaling factor which is used for the embedding. The proposed algorithm is implemented in MATLAB and simulation results demonstrated that proposed algorithm performs well in terms of PSRN and MSE.